Lactic acidosis, risk factors and predictive laboratory markers: A nested case control study in South Africa - C.A. Luke; M.Y.S. Moosa; T.M. Esterhuizen; S.E. Knight; S. Saman; A. Ross (South African Family Practice)
Background: The incidence of antiretroviral therapy (ART)-induced lactic acidosis and its associated mortality may be reduced by appropriate dosing, risk stratification and early detection.